Development of Supplementary Teaching Materials for Lower Plant Botany Based on Local Potential of Ferns (Pteridophyta) in Coastal Areas - Tuapattinaya, Prelly Marsel Jolanda; Papilaya, Pamella Mercy; Pradana, Sendy Putra (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
This study aimed to develop supplementary teaching materials for the Lower Plant Botany course in the form of a contextual resource integrating text, images, tables, and local examples to support independent learning on Pteridophyta based on the ecological potential of the coastal area of Waai Village, Maluku. The study employed a Research and Development approach using the Four-D (4D) model, consisting of define, design, develop, and disseminate stages. Ecological inventory data of coastal ferns served as the foundation of the material content. A total of nineteen fern species were identified and systematically integrated into the teaching materials to support contextual learning. Unlike previous local-potential-based materials, this product was developed from a systematic inventory of coastal fern species, allowing field-based ecological data to be transformed into instructional examples for higher education biology learning. The materials were evaluated through expert validation involving specialists in content, media, and language, as well as a student readability test with biology education undergraduates. The average expert validity score was 79.0%, indicating that the materials were valid with minor revisions, while student readability scores ranged from 92.00% to 95.00%, categorized as very good. Although learning effectiveness was not examined, the findings indicate that teaching materials derived from local ecological inventory data are feasible as contextual supplementary resources in preservice biology teacher education.